사체의 장골에서 수용부 형성방법에 따른 임플란트 일차 안정성 - 심정우; 조진용; 국민석; 박홍주; 오희균 (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2008)
This study was performed to evaluate the effect of the implant recipient site preparation methods on primary stability of implants with the instruments of OsstellTM and Periotest in the iliac bone of cadaver. Methods and materials: The 8 iliac bones in 4 cadavers and implants treated with resorbable blasting media (RBM) were used. Periotest (Simens AG, Germany) and OsstellTM(Model 6 Resonance Frequency Analyser: Integration Diagnostics Ltd., Sweden) were used to measure primary stability of implants. Implants were inserted into the iliac crest of the cadaver. In control group, the recipient site was prepared according to the manufacturer’s recommendation: 1.8 mm guide drill, 2.0 mm initial drill, 2.7 mm pilot drill, 2.7 mm twist drill, 3.0 mm twist drill, 3.3 mm pilot drill, 3.3 mm twist drill, and 3.3 mm countersink drill as well as tapping drill were used in order. In the group 1, implant recipient sites were prepared by sequentially drilling from 1.8 mm guide drill to 3.0 mm twist drill and then inserted implants without countersinking and tapping. In the group 2, implant recipient sites were prepared to 3.0 mm twist drill and countersink drill and then inserted implants without tapping. In the group 3, the sites were prepared to 3.0 mm twist drill and countersink drill as well as tapping drill. In the group 4, the sites were prepared to 3.3 mm twist drill. In the group 5, the sites were prepared to 3.3 mm twist drill and countersink drill. A total of 60 implants were placed (n=10). The stability was measured using OsstellTM and Periotest mesiodistally and buccolingually. To compare the mean stability of each group statistically, One-way ANOVA was used and correlation of instrument were analyzed using SPSS 12.0. The results obtained were as follows; 1. The stability of group 1 measured using OsstellTM and Periotest buccolingually showed the highest, and there are significant difference statistically between control group and experimental group 1,2,4 in each instruments respectively (p<0.05). 2. The stability of group 1 measured using OsstellTM and Periotest mesiodistally showed the highest. There are significant difference statistically between control group and all experimental groups in OsstellTM, and between control group and experimental group 1,2,3,4 (p<0.05). 3. There are high correlation between the measurements of OsstellTM and Periotest (p<0.05). Conclusion: These results indicate that the primary stability of implant can be obtained by the recipient sites preparation with smaller diameter drill than that of implant or minimal drilling. KCI Citation Count: 0